Perceptions and Difficulties of Distance Learning Among Beginning Teachers and Kindergarteners During the Covid-19 Pandemic Period - Zedan, Raed (Alberta Journal of Educational Research, 2024)
Exploring the perceptions and challenges faced by beginning teachers and kindergarten teachers in the realm of distance learning reveals critical insights into the evolving landscape of early education in a digital age. The present study explored the challenges and difficulties experienced by beginning teachers and kindergarteners in the context of distance learning. Qualitative research was conducted through semi-structured interviews involving 254 novice teachers and kindergarten educators. The findings revealed a range of difficulties new teachers face in the distance learning environment. These included challenges in conveying educational content, issues with Wi-Fi and internet connectivity, a lack of resources and technological tools, difficulties in engaging students in Zoom meetings, poor communication between teachers and students, insufficient preparation and training for distance teaching, inadequate digital skills, and a lack of experience among parents with the new method of learning. Understanding the challenges and difficulties that novice teachers encounter, particularly during their initial professional years and in exceptional circumstances like the COVID-19 pandemic, is crucial. This understanding not only aids in addressing and surmounting these challenges but also contributes to the enhancement and development of current distance teaching models. Such improvements should consider the specific needs and challenges of new teachers. L'étude des perceptions et des difficultés rencontrées par les enseignants débutants et les enseignants de maternelle dans le domaine de l'enseignement à distance révèle des informations essentielles sur l'évolution du paysage de l'éducation préscolaire à l'ère numérique. La présente étude a exploré les défis et les difficultés rencontrés par les enseignants débutants et les enseignants de maternelle dans le contexte de l'enseignement à distance. La recherche qualitative a été menée par le biais d'entrevues semi-structurées auxquelles ont participé 254 enseignants débutants et éducateurs de maternelle. Les résultats ont révélé une série de difficultés auxquelles les nouveaux enseignants sont confrontés dans le milieu de l'enseignement à distance. Il s'agit notamment des difficultés à transmettre le contenu éducatif, des problèmes de connexion Wi-Fi et Internet, du manque de ressources et d'outils technologiques, des difficultés à faire participer les élèves aux réunions Zoom, de la mauvaise communication entre les enseignants et les élèves, du manque de préparation et de formation à l'enseignement à distance, des compétences numériques inadéquates et du manque d'expérience des parents en ce qui concerne cette nouvelle méthode d'apprentissage. Il est essentiel de comprendre les défis et les difficultés que rencontrent les enseignants débutants, en particulier au cours de leurs premières années professionnelles et dans des circonstances exceptionnelles telles que la pandémie de COVID-19. Cette compréhension permet non seulement d'aborder et de surmonter ces défis, mais aussi de contribuer à l'amélioration et au développement des modèles actuels d'enseignement à distance. Ces améliorations devraient prendre en compte les besoins et les défis spécifiques des nouveaux enseignants.